GREEN SYNTHESIS AND APPLICATIONS OF SUPERPARAMAGNETIC IRON OXIDE NANOPARTICLES (SPIONS): A SUSTAINABLE APPROACH - Vijay Krishanan; Devasena, B; Swetha, M; Priya, S; Geetha, C (The Bioscan, 2025)
Iron oxide nanoparticles, particularly superparamagnetic iron oxide nanoparticles (SPIONs), have attracted considerable attention due to their unique magnetic properties, biocompatibility, and potential in biomedical and environmental applications. Traditional physical and chemical synthesis methods involve hazardous reagents and energy-intensive processes. Green synthesis, especially using plant extracts, offers a safer, eco-friendly, and cost-effective alternative. This review explores the various forms of iron oxide, their structural and magnetic characteristics, and recent advances in plant-mediated synthesis. The potential applications in imaging, drug delivery, environmental remediation, and biosensing are also discussed, emphasizing the advantages of sustainable nanoparticle production.